2017
DOI: 10.2214/ajr.16.17201
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Incidental Pulmonary Embolism

Abstract: The treatment of subsegmental PE may be guided by an assessment of patient symptoms, risk factors for recurrent venous thrombosis, and concomitant deep venous thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…Because early lung adenocarcinomas manifesting as subsolid nodules are considered to be more common in Asians than in the Occidental population (25), the prevalence of incidentally detected lung cancer among female never-smokers may be smaller in a different ethnic population than in our study patients. The reported frequency of incidental pulmonary embolism has increased over time with the introduction of CT machines (26)(27)(28). The prevalences of symptomatic and asymptomatic pulmonary embolism in our patient population were 0.2% and 0.4%, respectively, lower than the reported prevalence (3.1%-3.6% of patients with malignancy) of incidental pulmonary embolism (27,28).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Because early lung adenocarcinomas manifesting as subsolid nodules are considered to be more common in Asians than in the Occidental population (25), the prevalence of incidentally detected lung cancer among female never-smokers may be smaller in a different ethnic population than in our study patients. The reported frequency of incidental pulmonary embolism has increased over time with the introduction of CT machines (26)(27)(28). The prevalences of symptomatic and asymptomatic pulmonary embolism in our patient population were 0.2% and 0.4%, respectively, lower than the reported prevalence (3.1%-3.6% of patients with malignancy) of incidental pulmonary embolism (27,28).…”
Section: Discussioncontrasting
confidence: 57%
“…The reported frequency of incidental pulmonary embolism has increased over time with the introduction of CT machines (26)(27)(28). The prevalences of symptomatic and asymptomatic pulmonary embolism in our patient population were 0.2% and 0.4%, respectively, lower than the reported prevalence (3.1%-3.6% of patients with malignancy) of incidental pulmonary embolism (27,28). This discrepancy may be explained by different patient characteristics, including patient age, body mass index, race, and malignancy type.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The management of incidentally discovered or silent PE in patients without known VTE risk factors is controversial, as large prospective studies have not yet shown benefits of anticoagulation in these cases. 30…”
Section: Discussionmentioning
confidence: 99%
“…Management is uncertain due to a lack of high quality evidence. Anticoagulation is recommended if the patient has symptoms that could be attributable to the PE; the PE is located in the main, lobar and/or segmental pulmonary arteries; concurrent DVT is present; or the patient has active cancer . Anticoagulation may not be necessary if the patient has a single subsegmental PE and no additional VTE risk factors …”
Section: Unresolved Issuesmentioning
confidence: 99%